Multiple spin echo generation by gradients of the radio frequency amplitude: Two-dimensional nutation spectroscopy and multiple rotary echoes - Kimmich, Rainer; Ardelean, Ioan; Lin, Yung-Ya; Ahn, Sangdoo; Warren, Warren S. (The Journal of chemical physics, 1999)
NMR (nuclear magnetic resonance) nutation is treated with respect to demagnetizing-field effects on the evolution of spin coherences. A two-dimensional NMR nutation spectroscopy scheme is suggested consisting of a single radio frequency (RF) pulse and a free-evolution period. The RF pulse amplitude as well as the external magnetic field are assumed to be subject to gradients in the same but otherwise arbitrary direction. Cross peaks are predicted as frequency domain counterparts of multiple echoes. It is suggested to analyze the cross peak shape in terms of distributions of internal gradients arising from magnetic susceptibility inhomogeneities in heterogeneous samples. Furthermore, a pulse scheme solely based on gradients of the RF amplitude is treated resulting in the prediction of multiple rotary echoes as counterparts to the conventional rotary echo. The origin again is evolution in the presence of spatially modulated longitudinal magnetization in the tilted rotating frame.